2022
DOI: 10.3389/fevo.2021.795913
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic, Phylogenetic and Functional Diversity of Bird Assemblages in Urban Green Spaces: Null Model Analyses, Temporal Variation and Ecological Drivers

Abstract: Urban expansion is a pervasive driver of biodiversity loss. To understand the effects of urbanization on diversity, we investigated the response of bird taxonomic, phylogenetic, and functional diversity to urban green spaces’ characteristics in thirty-one green spaces of Mexico City. Selected sites encompassed variation of environmental factors along a transformation gradient, from natural protected areas to landscaped parks. Bird observations were conducted during winter (non-breeding season), spring (dry bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 91 publications
(99 reference statements)
1
6
0
Order By: Relevance
“…Studies of tropical forest biodiversity have shown that the species diversity of trees, shrubs and vines is mainly affected by patch shape (Yan et al 2021). In Mexico, research has shown a negative correlation between species richness and boundary shapes (Nava-Díaz et al 2022). Our research also showed that park diversity levels tend to decrease as the shape index increases, an indication of the complexity of the park.…”
Section: Effects Of Patch Characteristics On Species Diversity In Parkssupporting
confidence: 59%
“…Studies of tropical forest biodiversity have shown that the species diversity of trees, shrubs and vines is mainly affected by patch shape (Yan et al 2021). In Mexico, research has shown a negative correlation between species richness and boundary shapes (Nava-Díaz et al 2022). Our research also showed that park diversity levels tend to decrease as the shape index increases, an indication of the complexity of the park.…”
Section: Effects Of Patch Characteristics On Species Diversity In Parkssupporting
confidence: 59%
“…Systematically categorising functional traits, encompassing key aspects of avian behaviour like feeding habits, foraging heights, habitat preferences, nesting behaviours, and migratory tendencies, has been documented in previous studies (Corbelli et al, 2015;Nava-Díaz et al, 2022). This categorisation aimed to simplify the complexities of avian behaviour, facilitating a comprehensive analysis of functional diversity.…”
Section: Selection Of Functional Traitsmentioning
confidence: 99%
“…While the concept of incorporating UGS into city planning has long been understood, the importance of species diversity has only been recently brought to the fore ( Hunter et al., 2019 ). This is particularly important, as the diversity of animals in urban areas may be linked to the diversity of the plant life ( Hughes et al., 2022 ; Nava-Diaz et al., 2022 ; Benedetti et al, 2023 ). Therefore, understanding influences on urban plant diversity (UPD) is crucial as a driver of overall urban biodiversity.…”
Section: Introductionmentioning
confidence: 99%